The influence of transformational leadership and HR practices on employee innovative work behavior through psychological capital as a mediator in MSMEs - Asli, Salsabila Hasya; Malini, Helma; Daud, Ilzar; Iman Kalis, Maria Christiana; Fauzan, Rizky (Institute of Computer Science (IOCS), 2023)
This study examines the potential mediating role that psychological capital in the correlation between employees’ innovative work behavior, HR practices, and transformational leadership. According to this study's hypothesis, workers who experience the influence of transformational leadership and HR practices that use psychological capital as a mediating factor will be more likely to engage in creative work practices. Transformational leadership emphasizes leaders' ability to inspire and drive their followers, foster a workplace environment that promotes innovation. Employee innovation will also be promoted via HR practices about pay structures, professional growth, information exchange, and encouraging supervision. Employees who are proactive in developing and putting new ideas, solutions, and advancements into practice exhibit innovative work behavior. To bolster the developed hypotheses, Structural Equation Modeling (SEM-AMOS) is utilized in this study to investigate link between independent factors, dependent variables, and mediating variables. 234 people responded to the questionnaire used as the data collection method. The study's findings indicate that innovative work practices and employees' psychological capital are positively and significantly impacted by transformational leadership and HR practices. Psychological capital mediates HR Practices and employee innovative work behavior. Psychological capital does not exhibit a mediating role between innovative work behavior among employees and transformational leadership.